Exploring the Correspondence Between General Correctional Programming and Inmate Misconduct Using a Time-Course Framework - Linning, Shannon J. (International journal of offender therapy and comparative criminology, 2022)
Inmate misconduct continues to threaten safety and order within correctional institutions. Yet few studies have examined its longitudinal nature. In this paper we explore the correspondence between correctional programming and inmate misconduct. To do this, we draw from Linning et al.’s time-course framework devised to improve the design and evaluation of interventions by considering effects that can occur before, during, and after programming. We provide the first empirical demonstration of their framework using prisoner misconduct data collected from all Ohio prisons between January 2008 and June 2012. A cross-lagged panel analysis provides support for the use of a time-course framework. Results show that misconduct decreased during programming. However, we observed increases in misconduct prior to and following exposure to programming. Our results suggest that future work needs to improve our understanding of causal mechanisms of inmate misconduct and when their effects are expected.